Problems in Biotechnology research - Jamal, Parveen; Mohd. Salleh, Hamzah (IIUM Press, 2002)
To meet the challenges posed by the growing population of the world, biotechnology research is being pursued in all countries. In the area of medicine remarkable success has been achieved. It is believed that in future this trend will continue. In the area food also scientists and technocrats have shown considerable success, but in this area they have not received appreciation because of many objections. The paper discusses issues pertaining to biotechnology researches, because if these issues are not thoroughly discussed and problems are not hammered out, biotechnology researches will go on but will fail to serve the humanity